2020
DOI: 10.7759/cureus.7478
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Nodule Size and Prediction of Cancer: A Study at Tertiary Care Hospital in Saudi Arabia

Abstract: Background Thyroid nodules have become relatively common in clinical practice, and their prevalence increases with age. The majority of thyroid nodules are benign, with 5-15% being malignant. There are a number of well-established predictors of malignancy in thyroid nodules, but thyroid nodule size has been a cause for concern for many researchers and results of the studies are still controversial about their probability of malignancy. Up to the current knowledge, there is no published study that evaluates if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
(34 reference statements)
2
18
1
Order By: Relevance
“…( 6 ) suggest that size <2 cm is associated with an increased risk of well-differentiated thyroid cancer, which is also supported by Hadi et al. ( 19 ) However, Miller et al. ( 20 ) and Karman et al.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…( 6 ) suggest that size <2 cm is associated with an increased risk of well-differentiated thyroid cancer, which is also supported by Hadi et al. ( 19 ) However, Miller et al. ( 20 ) and Karman et al.…”
Section: Discussionmentioning
confidence: 59%
“…Irregular shape (taller than wide) was also usually contributed to predict the malignancy of the intermediate thyroid nodule (14,16,17). Nodule size is also reported to have predictive value of malignancy in several studies (8,18), and Jung et al (6) suggest that size <2 cm is associated with an increased risk of well-differentiated thyroid cancer, which is also supported by Hadi et al (19) However, Miller et al (20) and Karman et al (21) demonstrated that size >2 cm may be associated with thyroid malignancy. In our study, we found that nodule size in the malignant group is significantly smaller than that in the benign group, and on the multivariate analysis this factor was confirmed to be an independent predictor for malignancy and a threshold of approximately 1 cm in nodule diameter.…”
Section: Discussionmentioning
confidence: 69%
“…Our results indicated no significant relation between the nodule size and risk of malignancy. There is a controversy whether thyroid cancer risk rises with increasing nodule size [18,19]. It has also been mentioned that the impact of size on the nodule malignancy risk could be variable by histopathologic type of the thyroid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings, the size of the thyroid nodules was not identified as a potential predictor of malignancy in the peripherally calcified nodules. There are conflicting findings on the impact of size on thyroid cancer risk, and both positive and negative associations have been reported between size and malignancy risk [ 20 ]. In their study, Kamran et al .…”
Section: Discussionmentioning
confidence: 99%